Working Poverty in the Framework of the Work Anthropology: A Literature Review and Considerations on Care-related Labour - Scotognella, Francesco (European Scientific Journal, ESJ, 2022)
The phenomenon of working poverty is significant and involves an important percentage of population in many countries. This paper focuses on sketching, without being exhaustive, the state-of-the-art on working poverty in terms of definition and size. It also considers possible recent correlations of working poverty with the COVID-19 pandemic and with the rise of the digital labour platforms. This paper also shows the difference between labour, work, and action according to Hannah Arendt, together with the concept of anthropology of work of Maria Pia Chirinos. Finally, highlighting the pioneering works of Chirinos, the study suggests a picture in which human being, or a rational animal (Lat.: animal rationale; Gr.: zoon logon echon, ζῷον λόγοϛ ἔχων), essentially acts in endeavours, such as labour which is devoted to self-preservation and care. Under such picture, society should take into account the richness of the traditions and skills of different types of jobs and also in terms of minimal wage.